The arts and state governments : at arm's length or arm in arm? - Lowell, Julia, 1961- (RAND Corp., 2006)
Even though a majority of Americans claim to support public funding of the arts, state government spending on the arts is minimal--and may be losing ground relative to other types of state expenditures. Moreover, most state arts agencies, or SAAs, have not succeeded in convincing state government leaders that the arts should be integral to their planning for their states' futures. This report, the second in a series commissioned by The Wallace Foundation to cover the findings of a multiyear RAND Corporation study of SAAs' changing roles and missions, examines SAA leaders' efforts to more firmly establish their agencies' value to state government in a changing political and fiscal environment. Case studies of two SAAs are used to illustrate a more strategic approach to public management, and to clarify some of the risks and rewards of bringing the arts and political worlds closer together.